answersLogoWhite

0


Best Answer

(x - 3x - 6) / 6 = (3x + 2) / 2

∴2(3x + 2) = 6(3x + 2)

∴6x + 4 = 18x = 12

∴12x = -8

∴x = -2/3

User Avatar

Wiki User

โˆ™ 2009-07-28 03:53:58
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.81
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
2270 Reviews

Add your answer:

Earn +20 pts
Q: X minus 3X minus 6 divided 6 equals 3X plus 2 divided by 3?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked